The significance of personal learning environments (PLEs) in nursing education: Extending current conceptualizations. (January 2017) - Patterson, Christopher; Stephens, Moira; Chiang, Vico; Price, Ann M.; Work, Fiona; Snelgrove-Clarke, Erna
Abstract: Background: Personal learning environments (PLEs) have been shown to be a critical part of how students negotiate and manage their own learning. Understandings of PLEs appear to be constrained by narrow definitions that focus primarily on technological engagement with a range of web tools and associated applications. This paper addresses a gap in the literature around PLEs for students currently enrolled in undergraduate nursing degrees. Purpose: To provide in-depth insights into how undergraduate students of nursing manage and experience their learning. Methods: This was an international multi-site qualitative study, utilizing focus groups. A schedule of 10 questions and nominal group techniques were used. Findings: Whilst the focus groups took place in very different geographical locations, there were strong similarities in student understandings of effective PLEs. These went well beyond current technological definitions. Findings were organized into three major themes; technologies, learning modalities and influencing factors. Discussion: We propose a broader understanding of PLEs that acknowledges individual personal and cultural contexts which we call the personally significant learning environment (PSLE). There is a need for greater investigation of how students understand and systematize their PSLE. Conclusions: This paper and our findings will be of interest to educators, researchers and institutions for developing appropriate frameworks that may maximize learning outcomes, encourage cultural sensitivities and facilitate greater understandings of how to support students to create appropriate PSLEs. Highlights: Personal learning environments are usually defined by the use of digital technologies and web based tools. Student nurses identify an effective learning space as a mix of technologies, learning modalities and other factors. This paper expands the definition of PLE, proposing the new term personally significant learning environment.